An exploration of barriers of research-knowledge sharing: the lived-experiences of academics in higher education institutions in Amhara Regional State, Ethiopia - Yismaw Nigussie Mekuria; Amera Seifu Belayneh; Solomon Melesse Mengstie (Bahir Dar Journal of Education, 2023)
This study investigated the key barriers of research-knowledge sharing (RKS) that influence research-knowledge sharing practices among academics and the influence of top academic leaders on academics’ research-knowledge sharing behavior. It attempted to explore the nature of sharing research-knowledge in HEIs in general, and to examine the lived-experiences of academics that act as key barriers on RKS. Previous research findings revealed a lack of research into research-knowledge sharing in higher education (HE). Most importantly, how RKS barriers in the university influence the academics’ research-knowledge sharing practices has not yet been fully examined. Qualitative research method was employed to thematically analyze data collected from six academics and three top university managers, selected purposely, from three universities. Data were collected through semi-structured interviews. The findings indicated that key barriers of RKS in the Ethiopian public universities include: fear of losing power, lack of trust, fear of getting one’s ideas taken, unavailability of Intellectual Property (IP) protection, time constraint, and lack of confidence. Suggestions are made to improve certain aspects of research-knowledge sharing among academics in higher education institutions. Top university academic managers shall look into the findings to further improve the culture, structure and policy of research-knowledge sharing and the overall research productivity of universities in Amhara Regional State, Ethiopia. The findings of this study provide new insight into the field of research-knowledge sharing adding knowledge to the body of knowledge management and organizational culture. They are of great importance to research-leaders in HEIs to develop, improve and implement research-knowledge sharing strategies.